Rhodesia and FIFA: racial discrimination, political legitimacy and football, 1960 to 1980. (3rd April 2021) - Novak, Andrew
ABSTRACT: Rhodesia (colonial Zimbabwe) was a member of FIFA from 1965 until its suspension in 1970, playing a single qualifying match against Australia for the 1970 World Cup. Rhodesia was under sanctions as a result of the white minority regime's unilateral declaration of independence (UDI) from Great Britain, which affected athletes' ability to participate in international sport. Football was the most popular sport for the black majority, though like other sports it was organized around private clubs, allowing informal racial segregation to persist. The Football Association of Rhodesia (originally the Southern Rhodesian Football Association) was the official FIFA affiliate, though it faced persistent challenges to its control of Rhodesian soccer as a result of its white leadership. A new racially integrated organization, the National Football Association of Rhodesia (NFAR), became the controlling body for football under black leadership by the mid-1970s. NFAR became the Zimbabwe Football Association and was admitted to FIFA in 1980.